La cultura organizacional y su impacto en el desempeño laboral en los trabajadores de la cooperativa de ahorro y crédito San Antonio de Toacaso en el período 2022 – 2023 - Cóndor Anguisaca, Lizbeth Nicol (2023)
The present project, with the theme "Organizational Culture and its Impact on Labor Performance in the Workers of the San Antonio de Toacaso Savings and Credit Cooperative in the Period 2022 - 2023", had as a general objective: "Analyze the organizational culture and its impact on job performance with the application of research techniques and instruments that resulted in a specific action plan for the organization", the approach was quantitative, based on the use of numerical data, performance was described in relation to the organizational culture, applying a type of explanatory research rescuing the value criterion of the research since the study had not been applied before in the Cooperative.